Pelatihan Aplikasi NVivo untuk Riset Kualitatif Bidang Akuntansi kepada Para Peneliti di Universitas Dhyana Pura - Sihar Tambun; Riris Rotua Sitorus (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
The purpose of implementing this community service program is to improve the ability of researchers to conduct qualitative research using the NVivo 12 plus software. This activity was carried out through three stages, namely the planning stage, the implementation stage and the evaluation stage. The method used in the implementation of the event is the lecture and practice method. The resource persons who became instructors in this training were lecturers at the Universitas 17 Agustus 1945 Jakarta and lecturers at Universitas Esa Unggul, as a form of community service. This training is really needed by researchers at Dhyana Pura University because no one has mastered the use of this software properly. Data processing skills with the NVivo 12 Plus software are needed to help the process of completing qualitative research research more effectively. This training focuses on the use of software for processing data from interviews, processing data from news portals, YouTube social media and literature reviews. Evaluation was carried out at the end of the event by distributing questionnaires in the form of a Google form, to find out the level of mastery of the participants. There was an increase in software mastery for the majority of the training participants. The majority of participants were able to independently process data using the NVivo 12 plus software.